Surgical Management of the Undescended Testis: Recent Advances and Controversies - Elder, Jack S. (European Journal of Pediatric Surgery, 2016)
Undescended testis (UDT) is the most common disorder of sexual development in boys and affects 3.5% of male newborns. Although approximately half of newborn UDTs descend spontaneously, some boys develop an ascending testis later in childhood. Recent guideline recommendations advocate orchiopexy by 18 months of age to maximize potential for fertility and perhaps reduce the risk for testicular carcinoma in the future. For palpable testes, a standard inguinal approach is appropriate. However, the prescrotal approach is often effective for low inguinal testes and reduces surgical time and patient discomfort with an equivalent success rate in boys with an ascending testis. Some advocate monitoring until adolescence to determine whether the testis will spontaneously descend into the scrotum, but data do not support this approach. Instead, prompt orchiopexy is recommended. In boys with a nonpalpable testis, approximately 50% are abdominal or high in the inguinal canal and 50% are atrophic, typically in the scrotum. Routine inguinal/scrotal ultrasound is not recommended, although in an older boy who is overweight, it is appropriate. If the patient has contralateral testicular hypertrophy, scrotal exploration is appropriate, and removal of the testicular remnant and contralateral scrotal orchiopexy to prevent future contralateral testicular torsion is recommended. In most cases, diagnostic laparoscopy is advised to determine whether the testis is abdominal. For the abdominal testis, there are numerous treatment options. If the testis is mobile or a peeping testis just distal to the internal inguinal ring, standard one-stage laparoscopic or open orchiopexy should be attempted using the Prentiss maneuver. If the testicular vessels are short or the testis is not mobile, a two-stage Fowler–Stephens orchiopexy is appropriate. The second stage can be performed laparoscopically or open. Another option is microvascular testicular autotransplantation, which is a technically demanding procedure. Surgical results of abdominal orchiopexy are highly variable, short term, and highly subjective. Prospective clinical trials with follow-up into adolescence and adulthood are necessary to assess the success of various surgical approaches.
Keywords: orchiopexy; undescended testis; abdominal testis; retractile testis; Fowler–Stephens orchiopexy